A systematised review of the literature related to the use of deterrence and reciprocity messages as a nudge to influence tax compliance behaviour - Monageng, Nompumelelo (University of Pretoria, 2021)
Mini Dissertation (MCom (Taxation))--University of Pretoria, 2020.